THE IMPLEMENTATION OF PROMOTION FOOD SAGU IN SELAT PANJANG KABUPATEN KEPULAUAN MERANTI - Jumiatun, Siti; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Promotion is a way of communicating by companies or organizations to encourage or attract potential customers to buy products or services marketed.The purpose of this research is to know the implementation of promotion sago food conducted by related parties in Meranti Island Regency and the inhibiting factor in promotion implementation. This research uses qualitative method with descriptive approach, research subject is Industry, Trade, Cooperative and Small Medium Enterprises as Management Party, staff of Promotion Building and Craft Promotion, and Cooperation of Tourism Office, Youth and Sports of Meranti Islands Regency and additional informant, that are visitors. The data collection is made by a interview, observation, and documentation. The result of this research is manager Taman Satwa Kandi has done promotion trought four media namely advertising, sales promotion, publicity, and personal selling not good. The inhibiting factor faced by manager in the implementation of promotion trought four promotion mix in terms of market properties fund for limited promotion, less support package, less local awareness so no effort from local community to take part in this culinary promotion, and the quality of human resources that still needs to be improved with training on promotion. Keywords : promotion, food sagu